Adherencia y no adherencia terapéutica en pacientes hipertensivos y/o diabéticos tipo 2, en el Subcentro de Salud de Motupe - Cabrera Ramón, Mayra Elizabeth (2014)
The objective of determining adherence and factors related to nonadherence in patients with hypertension and / or type 2 diabetes in the Health Sub-Centre Motupe a cross-sectional study was conducted , the universe were all Diabetic patients and / or hypertensive treated at the outpatient clinic , 123 patients ; and the sample : all patients aged 18-89 years with Type 2 Diabetes Mellitus and / or Hypertension ; 63 patients . During the period January to June 2013 . Data collection was carried out by applying the test of modified Morinsky -green , consisting of a self- report on adherence to treatment. 52.38 % of the patients were previously adhered to the indicated therapy . The average age was 61-80 years , predominantly female , and mostly occupying Housework , Comprehensive Primary level instruction. Moderately adherent and non- adherent , patients had attributed factors relating to the patient , the disease , the treatment and the doctor- patient relationship. KEYWORDS : Diabetes, Hypertension , Therapeutic Adherence.